2011
DOI: 10.1111/j.1365-313x.2011.04771.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic evolution of herbivore‐induced sesquiterpene biosynthesis in sorghum and related grass crops

Abstract: ). † These two authors contributed equally to this work. SUMMARYSorghum (Sorghum bicolor) plants damaged by insects emit a blend of volatiles, predominantly sesquiterpenes, that are implicated in attracting natural enemies of the attacking insects. To characterize sesquiterpene biosynthesis in sorghum, seven terpene synthase (TPS) genes, SbTPS1 through SbTPS7, were identified based on their evolutionary relatedness to known sesquiterpene synthase genes from maize and rice. While SbTPS6 and SbTPS7 encode trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…ShZIS belongs to the ent-kaurene Terpene Synthase (TPS)-e/f subfamily (see ref. 19) and is not homologous to other zingiberene synthases, such as sweet basil ObZIS (16), Sorghum SbZIS (SbTPS1) (18), or to other tomato sesquiterpene synthases (19,20). However, both ShZIS and ShSBS are homologous to SlTPS19-20, which belong to an atypical class of monoterpene synthases in S. lycopersicum and Solanum pennellii (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ShZIS belongs to the ent-kaurene Terpene Synthase (TPS)-e/f subfamily (see ref. 19) and is not homologous to other zingiberene synthases, such as sweet basil ObZIS (16), Sorghum SbZIS (SbTPS1) (18), or to other tomato sesquiterpene synthases (19,20). However, both ShZIS and ShSBS are homologous to SlTPS19-20, which belong to an atypical class of monoterpene synthases in S. lycopersicum and Solanum pennellii (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, purified 7-epizingiberene, when applied to the headspace of susceptible cultivated tomato, repelled whiteflies, whereas α-zingiberene isolated from ginger did not (15). Although several zingiberene synthases have been identified (16)(17)(18), including one from S. habrochaites (7), we have now unambiguously identified and characterized 7-epizingiberene synthase from S. habrochaites and modified a cultivated tomato to produce 7-epizingiberene. Moreover, plants with improved herbivore resistance were obtained by traditional breeding and these may contribute to reduced pesticide use.…”
mentioning
confidence: 86%
“…However, some areas of plant specialized metabolism have received more attention in this respect. The terpenoid pathway leading to the synthesis of the specialized metabolites of the monoterpene, sesquiterpene, and diterpene classes (with skeletons of 10, 15, and 20 carbons, respectively; Figure 1A) is widespread in plants, and the organization of genes encoding terpene synthases (TPSs; a term designating the enzymes responsible for the synthesis of the basic skeleton structures of mono-, sesqui-, and diterpenes; Figure 1A) has been examined in several plant genomes (Chen et al, 2011;Zhuang et al, 2012). In Arabidopsis, a number of TPS genes are found in close association with other confirmed or putative terpenoid metabolism-related genes, for example, genes encoding geranylgeranyl diphosphate synthases (the enzyme that synthesizes the substrate for diterpene synthases; Figure 1A), cytochrome P450s (which often hydroxylate terpenes), and glycosyl transferases (Aubourg et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Kampranis et al (2007) altered the 1,8-cineole synthase of Salvia officinalis into an a-terpineol synthase and sesquiterpene synthase. Garms et al (2012) and Zhuang et al (2012) demonstrated that a single amino acid substitution near the active pocket altered the product outcome for the sesquiterpene synthases SbTPS1 and SbTPS2 of Sorghum bicolor. Here, we showed that a single amino acid mutation (F266S), changing the large aromatic side chain of Phe into the small, hydroxylated amino acid Ser, resulted in a significant reduction of the second cyclization reaction in the CIN of N. suaveolens (Fig.…”
mentioning
confidence: 99%